The timing of child physical maltreatment: A cross-domain growth analysis of impact on adolescent externalizing and internalizing problems - Keiley, Margaret K. (2001)
In a sample of 578 children assessed in kindergarten through the eighth grade, we used growth modeling to determine the basic developmental trajectories of mother-reported and teacher-reported externalizing and internalizing behaviors for three physical maltreatment groups of children—early-harmed (prior to age 5 years), later-harmed (age 5 years and over), and nonharmed—controlling for SES and gender. Results demonstrated that the earlier children experienced harsh physical treatment by significant adults, the more likely they were to experience adjustment problems in early adolescence. Over multiple domains, early physical maltreatment was related to more negative sequelae than the same type of maltreatment occurring at later periods. In addition, the fitted growth models revealed that the early-harmed group exhibited somewhat higher initial levels of teacher-reported externalizing problems in kindergarten and significantly different rates of change in these problem behaviors than other children, as reported by mothers over the 9 years of this study. The early-harmed children were also seen by teachers, in kindergarten, as exhibiting higher levels of internalizing behaviors. The later-harmed children were seen by their teachers as increasing their externalizing problem behaviors more rapidly over the 9 years than did the early- or nonharmed children. These findings indicate that the timing of maltreatment is a salient factor in examining the developmental effects of physical harm.